Situation Report: Romania, 14 June 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to Middle East Ceausescu's Visit to Yugoslavia Postponed Complaints and Demands of Young Romanian Philosophers World Literature Introduced in High School Curriculum Miscellaneous